An Innovative Aerial Manipulator with Tandem Ducted Fans: Modeling, Control, and Simulation - Yibo Zhang; Wei Fan; Changle Xiang; Bin Xu; Tianfu Ai; Lei Yuan; Yang Liu (Complexity)
This paper proposes an innovative ducted fan aerial manipulator, which is particularly suitable for the tasks in confined environment, where traditional multirotors and helicopters would be inaccessible. The dynamic model of the aerial manipulator is established by comprehensive mechanism and parametric frequency-domain identification. On this basis, a composite controller of the aerial platform is proposed. A basic static robust controller is designed via H-infinity synthesis to achieve basic performance, and an adaptive auxiliary loop is designed to estimate and compensate for the effect acting on the vehicle from the manipulator. The computer simulation analyses show good stability of the aerial vehicle under the manipulator motion and good tracking performance of the manipulator end effector, which verify the feasibility of the proposed aerial manipulator design and the effectiveness of the proposed controller, indicating that the system can meet the requirements of high precision operation tasks well.